A Review on Segmented Switched Reluctance Motors - Zhenyao Xu; Tao Li; Fengge Zhang; Yue Zhang; Dong-Hee Lee; Jin-Woo Ahn (Energies, 2022)
The switched reluctance motor (SRM) benefits from its magnet-free nature, robust construction, low cost, flexible controls, and the ability to operate in harsh environments such as high temperatures and high pressure. It has received increasing attention for all-electric or multi-electric aircraft systems and electric vehicles (EVs) as compared with permanent magnet synchronous motors (PMSM) and other AC motors in some required high reliability and fault tolerance applications. However, the SRM is prone to considerable wind resistance due to the convex pole structure of the rotor during high-speed rotation, high torque ripple, and also vibration noise. Thus, it is currently a trending topic to develop special SRMs, tailored with high reliability and fault tolerance. Recent research demonstrates several promising feasible solutions to reduce torque ripples and enhance torque density and power factors, including changing topology of SRM, using advanced control methods, as well as different winding configurations. Among these options, the segmented switched reluctance motor (SSRM), as a deformation of the conventional topology, is shown to be capable of effectively optimizing the torque performance. Motivated by this advance, this paper aims to present a comprehensive literature review on the SSRM, first illustrating the development of the topology of the SRM, then providing a description as well as a classification according to the topology of the SSRM. In particular, we focus on the evolution of various kinds of segmental topology and improvement measures. Then, we discuss the performance, advantages, and disadvantages of various types of structures in terms of their electromagnetic aspects and their applications. Eventually, several promising future trends and application prospects of the SSRM are prospected, with the aim of shedding light on further research. In sum, the key contribution of this paper is to provide a valuable basis for detailed analyses of the structure and electromagnetic design of the SSRM that are expected to benefit future research.